The Determinants of Non-Performing Loans in the MINT Economies - Morakinyo, Akinola Ezekiel; Sibanda, Mabutho (Journal of Economics and Behavioral Studies, 2016)
This paper investigates the major determinants of non-performing loans in the MINT (Mexico, Indonesia, Nigeria and Turkey) economies. Identifying major determinants of non-performing loans, which are observed to be growing in these countries in recent time, will also guide policy and forecasting future levels that will be useful for pre-emptive policies and actions. It uses static panel data and dynamic panel model analyses. Evidence suggests that in the four economies, capital adequacy ratio, liquidity ratio, total bank credit andreturn on assets are significant bank-specific determinants of non-performing loans. Also, while the return on assets, liquidity ratio and capital adequacy ratioshow a negative and significant relationship with non-performing loans, nominal exchange rate, money supply growth rate, total bank credit and lending rate show positive and very significant relationships with non-performing loans. Finally, corruption, an institutional variable, shows a very strong positive relationship with non-performing loans.